Evaluation of pro-vitamin A enriched maize hybrids for fighting hidden hunger in Nepal - Tripathi, Mahendra Prasad; Gautam, Damodar; Koirala, Keshab Babu; Shrestha, Hari Kumar; Issa, Abdurahman Beshir (Galaxy Science, 2022)
Prevailing vitamin A deficiency is a malnutrition repercussing retarded growth, weak immune system and night-blindness in human beings. Pro-vitamin A enriched maize hybrids could be a strategy for combating vitamin A deficiency, mostly prevailing in children and women of Nepal. With the objective to investigate superior pro-vitamin A enriched ‘bio-fortified’ maize cultivars, twice replicated experiments were laid out in α-lattice design over two consecutive growing seasons of 2019 and 2019/20 at the National Maize Research Program (NMRP), Rampur, Chitwan, Nepal. The results revealed that the difference among tested hybrids was glaring for all agro-morphological, yield, and yield components traits. Among the evaluated traits, days to 50% anthesis and silking, plant and ear height, numbers of kernel rows per cob, grains per row, and grain yield varied significantly among the tested maize hybrids. Effect of planting season was significant for grain yield where winter maize produced 32% higher grain yield than spring maize. HPO16-2, HPO49-3, HPO49-5, and HPO49-2 were the 38-61% high yielding ‘bio-fortified’ maize genotypes than normal hybrid check. Therefore, these hybrids might be the potential higher-yielding future pro-vitamin A enriched maize hybrids to resolve food insecurity, malnutrition, trade deficit on maize grains and specially to combat vitamin A deficiency in Nepal.